An Analysis of the Magazine Advertisement and Its Role: A Historical Evolution of Advertising in the Marketplaces (Journal of Advances and Scholarly Researches in Allied Education, 2013)
With the form of advertising, we could meet in themarketplaces, where the sellers used to shout and extol their products. In thecourse of time, people more and more tried to differentiate their products andbegan to find out new ways of presenting. They started to accentuate the visualaspect of the advertisement. With the expansion of colour printing and colorfulposters the streets began to revel in colors. These posters were ancestors toour modern billboards.